Strain Effect Study on Mode Field Diameter and Effective Area of WII Type Single Mode Optical Fiber - Makouei, S.; Makouei, F. (Advanced Electromagnetics, 2016)
In this article, the effect of strain on mode field diameter (MFD) and effective area (Aeff) in a modern multilayer WII type single mode optical fiber is investigated. The modal analysis of the fiber structure is based on linear polarized (LP) approximation method. The simulation results depict that both mode field diameter and effective area grow as a result of increment in tensile strain. The overall effect is observed in a slight rise in quality factor (Qf) of the fiber. Likewise, enlargement in amplitude of compressive strain leads to decrement in MFD and Aeff. However, among the optical and geometrical parameters of the fiber structure, Δ has the most considerable impact on both MFD and Aeff variation whilst R1 shows the least effect. In other words, any shift in the value allocated to Δ results in substantial change in the MFD and Aeff alteration due to strain. To eliminate this effect, the higher amounts for Δ are preferable which is related to the layering structure of the WII type optical fiber.